Pan-cancer analysis of Krüppel-like factor 3 and its carcinogenesis in pancreatic cancer - Zhu, Jinfeng; Teng, Hong; Zhu, Xiaojian; Yuan, Jingxuan; Zhang, Qiong; Zou, Yeqing (Frontiers in Immunology, 2023)
Background: Krüppel-like factor 3 (KLF3) is a key transcriptional repressor, which is involved in various biological functions such as lipogenesis, erythropoiesis, and B cell development, and has become one of the current research hotspots. However, the role of KLF3 in the pan-cancer and tumor microenvironment remains unclear.Methods: TCGA and GTEx databases were used to evaluate the expression difference of KLF3 in pan-cancer and normal tissues. The cBioPortal database and the GSCALite platform analyzed the genetic variation and methylation modification of KLF3. The prognostic role of KLF3 in pan-cancer was identified using Cox regression and Kaplan-Meier analysis. Correlation analysis was used to explore the relationship between KLF3 expression and tumor mutation burden, microsatellite instability, and immune-related genes. The relationship between KLF3 expression and tumor immune microenvironment was calculated by ESTIMATE, EPIC, and MCPCOUNTER algorithms. TISCH and CancerSEA databases analyzed the expression distribution and function of KLF3 in the tumor microenvironment. TIDE, GDSC, and CTRP databases evaluated KLF3-predicted immunotherapy response and sensitivity to small molecule drugs. Finally, we analyzed the role of KLF3 in pancreatic cancer by in vivo and in vitro experiments.Results: KLF3 was abnormally expressed in a variety of tumors, which could effectively predict the prognosis of patients, and it was most obvious in pancreatic cancer. Further experiments verified that silencing KLF3 expression inhibited pancreatic cancer progression. Functional analysis and gene set enrichment analysis found that KLF3 was involved in various immune-related pathways and tumor progression-related pathways. In addition, based on single-cell sequencing analysis, it was found that KLF3 was mainly expressed in CD4Tconv, CD8T, monocytes/macrophages, endothelial cells, and malignant cells in most of the tumor microenvironment. Finally, we assessed the value of KLF3 in predicting response to immunotherapy and predicted a series of sensitive drugs targeting KLF3.Conclusions: The role of KLF3 in the tumor microenvironment of various types of tumors cannot be underestimated, and it has significant potential as a biomarker for predicting the response to immunotherapy. In particular, it plays an important role in the progression of pancreatic cancer.